Лікування та реабілітація хворих на рак щитоподібної залози з інвазією у верхні дихальні шляхи - Дейнеко, І. В.; Кутовий, О. Б.; Тимчук, С. М.; Люлько, І. В.; Кравченко, В. А. (Clinical Endocrinology and Endocrine Surgery, 2010)
Treatment and rehabilitation of thyroid cancer patients with an invasion in upper airways remains unsatisfactory. The method of radical surgical treatment of such patients is offered. This method includes an extrafascial thyroidectomy with the resection of the affected areas of upper airways, and the subsequent stage-by-stage reconstruction of their lumen and single-stage lateral fixation of vocal fold with paresis. It allowed promoting efficiency of treatment and rehabilitating patients functionally.